Optimización del sistema de explotación para la extracción de materiales áridos y pétreos del área minera “Yuma, código 600011”, sector Nangóra, parroquia Malacatos cantón y provincia de Loja. - Pachar Bravo, Evelyn Patricia (2018)
The research and development of mining is one of the important sources of income and sustained progress of a people, a country and the entire world. Non-metallic minerals and industrial rocks, including construction materials, constitute an important percentage of the raw material required by the different branches of industry in our country. The arid and stone materials are the fundamental raw material in urban development and construction, with the supply and demand of this type of resources increasing. With the theme of Optimization of the exploitation system for the extraction of arid and stony materials from the mining area "Yuma, code 600011", place Nangora, parish of Malacatos canton and province of Loja; It is intended that the work of extraction of aggregates be systematic and effective this with the purpose that the impact is minimal without altering the endemic conditions of the place, also considering the processes that allowed to give an optimization criterion with respect to the mode of operation of phase at work. The processes, their description corresponding to the exploitation system were carried out by means of the on-site visit, recording all the activities in photographs and notes detailing machinery used and mode of operation. The characteristics of the current processes are evidently insufficient, extractions are carried out under inadequate conditions, considering that in areas the accumulated material is again dragged along the channel, which in rainy seasons the water level is sufficient for the aforementioned to be fulfilled, reason why which proposes an alternative that regulates and optimizes the processes in this mining area.